Assessing Workspaces of Office Buildings; A Case of Lagos Office Spatial Characteristics - Deborah Oluwabunmi Alonge; Stella Zubairu; Isa Bala Muhammad (International Journal of Environmental Planning and Development Architecture, 2023)
The spatial characteristics of an office space play a fundamental role in contributing to the performance of the employees who use the office space. An efficient and functional workspace should be designed to cater to the needs of employees as this is critical to their performance as well. Studies from various authors have shown that better results and outcomes are gotten from employees who are satisfied with their workspaces. Although in recent times, the spatial configuration of the workspace has proven to be insufficient as employees are seen to be less productive. This paper aims to assess workspace performance by identifying the spatial characteristics of the spaces employees work. This will be achieved by categorizing the workspace by its makeup. The paper assessed six (6) office buildings where 105 different office types were observed. Qualitative data was gotten and descriptively analysed. The result showed two major domains characterized by the offices in Lagos; physical and functional domains.
Keywords: Office building; Performance; Spatial Characteristics; Utilisation; Workspace